2021
DOI: 10.1002/ptr.7097
|View full text |Cite
|
Sign up to set email alerts
|

In silico approach of secondary metabolites from Brazilian herbal medicines to search for potential drugs against SARS‐CoV‐2

Abstract: The new severe acute respiratory syndrome coronavirus (SARS‐CoV‐2) recently emerged as a worrying pandemic, with many confirmed cases and deaths globally. Therefore, there is a clear need for identifying effective therapeutic options and a review of secondary metabolites related to Brazilian herbal medicines was performed as a strategy for the discovery of new antiviral agents. To confirm this potential, an in silico screening of the identified compounds identified was also evaluated. The review was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…35,36 Another research, including Brazilian, Peruvian, and Mexican herbal medicines from the American continent were also reported for having potential against SARS-CoV-2. [37][38][39] Another point of view, numerous African medicinal plants were reported by researchers. [40][41][42][43] Our former study revealed that an herbal combination of Moringa oleifera and Curcuma longa could be an antiviral agent via dual inhibitors pathway for SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 Another research, including Brazilian, Peruvian, and Mexican herbal medicines from the American continent were also reported for having potential against SARS-CoV-2. [37][38][39] Another point of view, numerous African medicinal plants were reported by researchers. [40][41][42][43] Our former study revealed that an herbal combination of Moringa oleifera and Curcuma longa could be an antiviral agent via dual inhibitors pathway for SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…It was exhibited that rutin has some inhibitory effect on SARS-CoV-2 proteins . Phytochemicals from the traditional medicines were also investigated by docking, such as those from traditional Himalayan medicinal plants, Indian traditional medicinal plants, Chinese traditional medicines, and Brazilian herbal medicines …”
Section: Methods and Approachesmentioning
confidence: 99%
“…318 Phytochemicals from the traditional medicines were also investigated by docking, such as those from traditional Himalayan medicinal plants, 319 Indian traditional medicinal plants, 320−333 Chinese traditional medicines, 334 and Brazilian herbal medicines. 335 Targeting Mpro, S protein, and RdRp, Parvez et al 298 studied some plant metabolites. Maurya et al 336 investigated yashtimadhu (glycyrrhiza glabra) active phytochemicals, and Alexpandi et al 337 simulated quinoline-based inhibitors.…”
Section: Orf9bmentioning
confidence: 99%
“…A review of secondary metabolites related to Brazilian herbal medicines followed by in silico evaluations indicated 19 potential anti‐SARS‐CoV‐2 compounds, mainly triterpenes and phenolic compounds. The indicated compounds showed a high affinity with proteins considered as the main molecular targets against SARS‐CoV‐2 (Amparo et al, 2021 ).…”
Section: Traditional Medicinementioning
confidence: 99%
“…The indicated compounds showed a high affinity with proteins considered as the main molecular targets against SARS-CoV-2 (Amparo et al, 2021).…”
mentioning
confidence: 99%